Explanation of factors forming missed nursing care during the COVID-19 pandemic: A qualitative study - Safdari, Ali; Rassouli, Maryam; Elahikhah, Maryam; Ashrafizadeh, Hadis; Barasteh, Salman; Jafarizadeh, Raana; Khademi, Fatemeh (Frontiers in Public Health, 2023)
Background Providing nursing care to patients with COVID-19 has put additional pressure on nurses, making it challenging to meet several care requirements. This situation has caused parts of nursing care to be missed, potentially reducing the quality of nursing care and threatening patient safety. Therefore, the present study aimed at explaining the factors forming missed nursing care during the COVID-19 pandemic from the perspective of nurses. Methods This qualitative study was conducted using a conventional content analysis approach in Iran, 2020–2021. Data were collected from in-depth, semi-structured interviews with 14 nurses based on purposive sampling. Data analysis was performed simultaneously with data collection. Graneheim and Lundman's approach was used for data analysis, and MAXQDA software was used for data management. After transcribing the recorded interviews, to achieve the accuracy and validity of the study, the criteria proposed by Lincoln and Guba were considered and used. Results A total of 14 nurses with a mean age and standard deviation of 31.85 ± 4.95 and working in the COVID-19 wards participated in the study. The acquired data were categorized into four main categories: care-related factors, disease-related factors, patient-related factors, and organization-related factors. The category “care-related factors” comprised uncertainty in care, PPE-related limitations, attrition from care, and futile care. The category “disease-related factors” consisted of the extension of symptoms, unpredictable peaks of the disease, and restriction on the presence of patients' companions. The category “patient-related factors” included comorbidities, elderly patients, and deterioration of infected patients. Ultimately, the category “organization-related factors” consisted of restrictions on equipment supply, lack of human resources, weaknesses in teamwork, and an unsupportive work environment. Conclusion The results of this study showed that several reasons including factors related to care, patient, disease, and organization cause missed nursing care. By modifying the related affecting factors and considering the effective mechanisms to minimize missed nursing care, it is possible to provide better services.